Rosacea and Anxiety Disorders - Psychosocial Impact, Quality of Life and Integrated Management - Radziszewska-Trojniak, Angelika; Włodarczyk, Michał (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Rosacea is a chronic inflammatory facial skin disease that may be associated with significant psychosocial burden. Studies indicate that affected individuals may experience anxiety, reduced self-esteem and lower quality of life compared with the general population. This review aims to summarize current evidence on the epidemiology, pathophysiology, psychosocial impact and integrated management of rosacea with coexisting anxiety disorders. Materials and methods: A literature review was performed using PubMed and Google Scholar, focusing on English-language publications. Priority was given to systematic reviews, meta-analyses, randomized controlled trials and observational studies. State of knowledge: Rosacea is a common chronic inflammatory skin disease in adults, more frequently reported in women and individuals with fair skin. Its etiopathogenesis is thought to involve immune dysregulation, neurovascular abnormalities and skin-brain axis dysfunction. Facial manifestations are associated with an increased risk of social anxiety, internalized stigma and reduced quality of life. Studies indicate that patients with rosacea may have an over twofold increased risk of anxiety disorders compared with the general population. Evidence suggests that dermatological treatment, combined with cognitive-behavioral therapy and stress management, can improve skin symptoms and psychological well-being. Conclusions: The bidirectional link between rosacea and anxiety disorders highlights the need for holistic management. Combining dermatological treatment with mental health assessment and psychological support may improve quality of life, reduce psychosocial burden and help interrupt the cycle of stress and disease exacerbation.